Political Behavior of Nasdem Party Elites Ahead of the 2024 Presidential Election in Pangkep Regency - Saifullah Bonto; Mudiyati Rahmatunnisa; Ratnia Sholihah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
This article aims to describe and analyze the political behavior of the Nasdem Party elite ahead of the 2024 Presidential Election in Pangkep Regency. This research is motivated by the phenomenon of the departure of party cadres that occurred in Pangkajene and Kepulauan (Pangkep) Regency, South Sulawesi. The method used in this article is a qualitative research method with a phenomenological approach. The results of this study indicate that the elite of the Pangkep Nasdem Party tend to show accommodating political behavior. Although the elite of the Pangkep Nasdem Party tend to only follow formal party instructions, the communication pattern built by the elite of the Pangkep Nasdem Party is inclusive and open, both communication to leaders at the level above them and leaders at the level below them. The elite of the Nasdem Party provide space for its cadres if they have different interests to determine their own choices at their own risk. The elite of the Pangkep Nasdem Party also show less political pragmatism. The nomination of Anies Baswedan as presidential candidate and Muhaimin Iskandar as vice presidential candidate is not based on the lure of positions or seeking positions by the Nasdem Party elites but solely because of the party's decision and the vision and mission carried by the Presidential and Vice Presidential Candidate Pairs.